Entropy optimization and heat transfer modeling for Lorentz forces effect on solidification of NEPCM. (October 2020) - Shah, Zahir; Hajizadeh, Mohammed Reza; Ikramullah,; Alreshidi, Nasser Aedh; Deebani, Wejdan; Shutaywi, Meshal
Abstract: In this research work, we study the solidification of nanoparticles-enhanced phase change material (NEPCM) in a latent heat thermal energy storage system (LHTESS) in the existence of magnetic field through entropy optimization. The Finite element method (FEM) is applied for solving the developed equations. Koo–Kleinstreuer–Li model is used to model the nanoparticles characteristics. The impacts of varying strength of magnetic field and buoyancy forces on solidification are examined. It is obtained that the rising Lorentz force due to augmenting Hartmann number enhances the solidification rate of NEPCM, while the enhancing buoyancy forces mitigates this rate of solidification. The Bejan number (Be) augments with the higher Lorentz forces while drops with the augmenting Buoyancy forces. The entropy generations due to the frictional forces and the applied B -field augment with the rising buoyancy forces while depreciate with the rising Hartmann number. The agreement between our and already published work confirms the accuracy of the applied computational technique. The results of this research work have potential applications in modeling the efficient thermal energy transfer systems by using nanofluids.